Model predictive control for MPPT of distributed photovoltaic module - Jowalin, Wellfred (2017)
Due to stochastic characteristics of solar energy which related to irradiation and temperature, a maximum power point of a PV panel was difficult to harvest. To overcome this problem, a maximum power point tracker (MPPT) used to continuously obtain the possibly maximum power point (MPP) of the solar panel produce. Many techniques used in the previous study commonly Perturb and Observe (P&O). Unfortunately, a P&O algorithm does not harvesting a true MPP of the PV panel during the operation. In this paper, a technique of MPPT using model predictive control (MPC) in renewable energy sources of photovoltaic (PV) module explained. In the PV system consists of PV module, a power converter which in this project was boost converter using a metal-oxide semiconductor field-effect transistor (MOSFET) as a switch, a MPC acts as MPPT to track the MPP. A PV panel consists of several cells, a boost converter and a MPC was designed using MATLAB/Simulink software due to the software provided enough toolbox and also Graphical User Interface (GUI). The main function of MPC used in PV system was to regulating a boost converter from an unregulated output produce by the renewable energy source of photovoltaic module by predict the future input and give appropriate duty cycle to the boost converter to harvest the possible maximum power point of the PV panel. A conventional P&O technique was design by develop the algorithm to compare the result. A plant using system identification developed as the MPC needs a plant for prediction. A couple of troubleshooting process was done to match the desired output. A slightly inaccurate result for MPC technique due to the plant develops in system identification.